USING AN ANIMATION FILM “ZOOTOPIA” AS AN ALTERNATIVEMEDIUM TO TEACH VOCABULARY - Endah Kartika Suryani; Sri Wuli Fitriati; Arif Suryo Priyatmojo (JELLT (Journal of English Language and Literature Teaching), 2021)
The aim of this study is to find out the effectiveness of using animation film “Zootopia” to teach vocabulary to improve students’ achievement in vocabulary mastery. This study is conducted in SD Labschool Universitas Negeri Semarang and the samples are taken from population of the third grade students in the academic year of 2016/2017. This study applied quasi-experimental research design. The population of this study was the third grade students of SD Labschool Universitas Negeri Semarang in the academic year of 2015/2016. Meanwhile, the sample consisted of 34 students from two classes. The study was started by giving pre-test, treatments, and post-test to both groups. The experimental group (3A) was taught by animation film entitled “Zootopia”, while the control group was taught by regular technique. The data were obtained by giving test to both groups. The pre-test result showed the average score from two groups, 71.13 for experimental group and 72.06 for control group. It meant both groups in the same level. After having treatments, the mean of the experimental group was 87.50 and the control group was 80.39. The results showed a lot improvement in group that got treatment using “Zootopia film (experimental group) than the group that got regular treatment. The independent sample result of post-test showed that the significant different level (2-tailed) was 0.03. Since Sig. (2-tailed) was lower than α = 0.05 (pvalue > 0.05), it could be concluded that there was significant difference from experimental and control groups. From the result above, it was concluded that the treatment given in the experimental group achieved an enhanced result. There was significant difference of students’ vocabulary mastery scores through Zootopia movie. The different means between pre-test and post-test was statistically significant. Thus, the use of Zootopia film toward the students’ mastery English vocabulary at the third grade students in SD Labschool Universitas Negeri Semarang in academic year 2016/2017 was significantly effective and it would give long-term assistance for the students.